PENGEMBANGAN OBJEK WISATA PADA QUEEN STAR WATERPARK DI KABUPATEN SIAK - Velicia, Deflin; Yulia, Nur Arini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This study aims to examine the development of Queen Star Waterpark as a tourism destination located in Siak Regency, Riau Province. Queen Star Waterpark is an artificial tourist attraction with great potential to support the local tourism sector's growth. This research uses a qualitative descriptive method with data collection techniques including observation, interviews, and documentation. The findings reveal that Queen Star Waterpark has met the 4A components of tourism development: Attraction, Amenities, Accessibility, and Ancillary Services. However, several challenges remain, such as damaged facilities and a lack of supervision in pool areas. Innovation and improvement in attraction management and supporting facilities are needed to keep this destination appealing and competitive. This study is expected to contribute to the enhancement of the quality and sustainability of water tourism in Siak Regency. Keywords: Tourism Development, Queen Star Waterpark, 4A Components, Siak Regency.